Carpal Tunnel Release Surgery and Venous Hypertension in Early Hemodialysis Patients without Amyloid Deposits. (5th November 2013) - Kocyigit, Ismail; Unal, Aydin; Guney, Ahmet; Mavili, Ertugrul; Deniz, Kemal; Kocyigit, Merva; Sipahioglu, Murat; Eroglu, Eray; Tokgoz, Bulent; Gunal, Ali Ihsan; Oymak, Oktay
Abstract : Aim . Carpal tunnel syndrome (CTS) is one of the frequent problems of the patients who underwent hemodialysis (HD). The role of venous hypertension due to arteriovenous fistula (AVF) has not been clarified completely; therefore, we aimed to investigate the role of venous hypertension due to AVF in hemodialysis patients who had CTS. Patients and Methods . We included 12 patients who had been receiving HD treatment for less than 8 years and the newly diagnosed CTS patients with the same arm of AVF. All patients were diagnosed clinically and the results were confirmed by both nerve conduction studies and electromyography. Open carpal tunnel release surgery was performed on all of them. Venous pressure was measured in all patients before and after two weeks of surgery. Results . There were significant differences before and after the surgery with regard to pressures (P > 0.05 ). After the surgery, all carpal ligament specimens of the patients were not stained with Congo red for the presence of amyloid deposition. Conclusion . Increased venous pressure on the same arm with AVF could be responsible for CTS in hemodialysis patients. Carpal tunnel release surgery is the main treatment of this disease by reducing the compression on the nerve.